Checklist of terrestrial Parasitengona mites in Fennoscandia with new species- and distribution records (Acariformes: Prostigmata) - Stalstedt J; Laydanowicz J; Lehtinen PT; Bergsten J; Makol J (PENSOFT PUBLISHERS, 2022)
BackgroundThe knowledge of terrestrial Parasitengona in Fennoscandia lies far behind that of their aquatic counterparts, the water mites (Hydrachnidia). Based on new inventories, we provide primary data and an annotated checklist of terrestrial Parasitengona in Fennoscandia including 107 species. Out of these, nineteen species are new findings for the region and five are species potentially new for science. Twenty-three species are new for Norway, fourteen for Finland and eleven for Sweden. The known recorded fauna today of terrestrial Parasitengona is 80 species for Norway, 54 for Sweden and 48 for Finland. Primary data include georeferenced locality data as well as collecting techniques and microhabitat to increase the knowledge on species' habitat requirements.